Investigation of GAS Gain of GEM-Foil Used in Low Energy Radioactive Beam Experiments - Duy, Nguyen Ngoc; Khiem, Le Hong (Communications in Physics, 2012)
Study of nuclear reactions using radioactive beams at low energy plays an important role in nuclear astrophysics and nuclear structure. The trajectory of particle beams can be obtained by using an active gas target, multiple-sampling and tracking proportional chamber (MSTPC). Because of low intensity of radioactive beam when studying the stellar nuclear reactions such as (α, p), (p, α),… it is necessary to increase the gain of the tracking counter system. A Gas Electron Multiplier (GEM) foil and the proportional counter called as GEM-MSTPC have been used for this purpose. In this study, the dependence of the effective gas gain of GEM foils on the foil thickness and on the operating pressure was investigated. Two types of GEM foil with the thickness of 400 μm and 200 μm in Argon (70%) – Carbon dioxide (30%) mixture have been used. This investigation is important for our direct measurement of 22Mg(α, p) reaction, which is planed to perform in 2012 at RIKEN.